2004
DOI: 10.1093/humrep/deh378
|View full text |Cite
|
Sign up to set email alerts
|

An increase in the absolute count of CD56dimCD16+CD69+ NK cells in the peripheral blood is associated with a poorer IVF treatment and pregnancy outcome

Abstract: An increase in the absolute count of activated NK cells (CD56(dim)CD16(+)CD69(+)) in the peripheral blood is associated with a reduced rate of embryo implantation in IVF treatment. Furthermore, women with high CD56(dim)CD16(+)CD69(+) peripheral blood NK cell absolute count, who are able to achieve pregnancy, have a significantly higher miscarriage rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 31 publications
(36 reference statements)
4
51
0
Order By: Relevance
“…Interestingly, they found that the peripheral CD56 bright dNK expressed higher NKp46 than CD56 dim dNK, which paralleled with what we found in decidual NK cells. Previous reports found that the peripheral CD56 þ CD16 þ dNK increased and CD56 þ CD16 À dNK decreased in patients who failed IVF-embryo transfer and had miscarriages (35,36), which paralleled with what was found in decidual of patients with SA (30)(31)(32). These reports could explain the lower level of CD56 þ /NKp46 þ dNK cells in patients with recurrent SA found in the study by Fukui et al In our study, we determined the expression of NKp46 on CD56 bright CD16 À dNK and CD56 dim CD16 þ dNK.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, they found that the peripheral CD56 bright dNK expressed higher NKp46 than CD56 dim dNK, which paralleled with what we found in decidual NK cells. Previous reports found that the peripheral CD56 þ CD16 þ dNK increased and CD56 þ CD16 À dNK decreased in patients who failed IVF-embryo transfer and had miscarriages (35,36), which paralleled with what was found in decidual of patients with SA (30)(31)(32). These reports could explain the lower level of CD56 þ /NKp46 þ dNK cells in patients with recurrent SA found in the study by Fukui et al In our study, we determined the expression of NKp46 on CD56 bright CD16 À dNK and CD56 dim CD16 þ dNK.…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, women with repeated pregnancy loss were found to have a lower percentage of endometrial CD56bright CD16À uNK cells and a higher percentage of CD56dim CD16þ uNK cells, with a greater cytolytic activity, when compared with control patients (1,7). An increase of activated NK cells (CD56dim CD16þ CD69þ) in the peripheral blood of patients with a reduced rate of embryo implantation in IVF treatment has been reported by several investigators (8)(9)(10)(11), but whether the percentage and phenotype of endometrial leukocytes are altered in those patients has not been extensively explored. We evaluated, by flow cytometry, endometrial lymphocyte subpopulations in young patients who were undergoing IVF cycles for idiopathic infertility with a history of repeated unexplained implantation failure.…”
mentioning
confidence: 75%
“…Several studies reported an increase of activated NK cells (CD56dim CD16þ CD19þ) in the peripheral blood of patients with a reduced rate of embryo implantation in IVF treatment (8)(9)(10)(11). Fukui et al (20) reported a significant increase in the percentage of cytotoxic NK cells, on the day of embryo transfer, in the peripheral blood of patients with implantation failure when compared with their implanted counterparts.…”
Section: Figurementioning
confidence: 99%
“…When patients with these abnormalities are treated with immunotherapy, results have been encouraging (Carp, 2007;Clark et al, 2006;Winger et al, 2011aWinger et al, , 2011b. However, the immunological assays employed have low specificity and sensitivity (Lee et al, 2013;Thum et al, 2004). In addition, these assays specifically fail to predict the risk of late term pregnancy complications such as preeclampsia and preterm birth.…”
Section: Introductionmentioning
confidence: 99%